Strategi Marketing Politik DPD Gerindra Jawa Barat Melalui Sayap Pira Pada Pemilu 2024 - Widdy Yuspita Widiyaningrum; Fuziah Nur Alifah (Jurnal Agregasi, 2023)
Gender disparity within the political sphere continues to persist. Therefore, the effective implementation of a law regarding the representation of women at a rate of 30% is necessary. The Gerindra’s woman under bow, PIRA (Perempuan Indonesia Raya), serves as a platform for women to enter the political arena and act as representatives of society. Based on this premise, the researcher conducted a study on the political marketing strategies employed by the PIRA to meet the 30% affirmative action quota in the upcoming 2024 general elections. The objective of this research is to determine the extent to which the PIRA achieves 30% female representation in politics. This study adopts a qualitative methodology with a narrative approach. The primary research subjects include party representatives, PIRA members, and PIRA representatives, selected through purposive sampling techniques. The research findings indicate that the Gerindra Party, through the PIRA, employs approaches such as online and offline media engagement, community service, and the influential presence of Prabowo as a means to garner significant support in the upcoming 2024 general elections.